Central-to-Folding Chirality Control: Asymmetric Synthesis of Multilayer 3D Targets With Electron-Deficient Bridges - Jin, Shengzhou; Wang, Jia-Ying; Tang, Yao; Rouh, Hossein; Zhang, Sai; Xu, Ting; Wang, Yu; Yuan, Qingkai; Chen, Daixiang; Unruh, Daniel; Li, Guigen (Frontiers in Chemistry, 2022)
New multi-layer 3D chiral molecules have been designed and synthesized asymmetrically through the strategy of center-to-multilayer folding chirality control and double Suzuki-Miyaura couplings. Individual diastereoismers were readily obtained and separated via flash column chromatography. The key diastereoisomer was further converted into corresponding enantiomers. These enantiomers possess electron-deficient aromatic bridges layered by top and bottom aromatic scaffolds. X-ray structural analysis has unambiguously confirmed the configuration, and intermolecular packing results in regular planar patterns in solid crystals. An overall yield (0.19%) was achieved in a total of ten-step synthesis starting from commercially available starting materials.